Synthesis and Characterization of Biocompatible Facial Sheet Masks Utilizing Ginger Cellulose and Jicama Starch - Adristi Nisazarifa; Yati Mardiyati; Steven Steven (BRIN Publishing (Penerbit BRIN), 2026)
Sheet masks are one of the most widely used beauty products to improve skin health. The increase in sheet mask usage leads to an increase in its waste, while some of the sheet masks contain synthetic fibers that are not biodegradable in the environment. Many researchers have been interested in innovating sheet masks by using natural polymer materials. Starch and cellulose were chosen because they are potentially environmentally friendly and biocompatible products. The solution casting method is used to produce sheet masks. Ginger cellulose and jicama starch were mixed, and the mass ratios of cellulose and starch are 100:0, 100:20, 100:40, 100:60, and 100:80. The addition of starch to cellulose tends to decrease the tensile strength and increase the percent elongation of the sample. The sample with a 100:0 ratio had the highest tensile strength at 34.75 MPa, while the highest percent elongation was achieved by the sample with a 100:40 ratio, measuring 4.80%. The absorption index of the sample to serum decreased with increasing starch composition. Samples with a mass ratio of cellulose to starch of 100:0, 100:20, and 100:40 exhibited better biodegradability than commercial sheet masks. Most of the samples undergo 100% biodegradation after 12 days of the biodegradation test. This research aims to develop a sheet mask made from ginger cellulose and jicama starch, which has flexible properties that allow it to conform to the shape of the face while also effectively absorbing serum or essence. This research can be used as an alternative for choosing sheet mask materials as a way to reduce plastic waste.